2020
DOI: 10.1016/j.dcn.2020.100849
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood violence exposure and social deprivation predict adolescent amygdala-orbitofrontal cortex white matter connectivity

Abstract: Childhood adversity is heterogeneous with potentially distinct dimensions of violence exposure and social deprivation. These dimensions may differentially shape emotion-based neural circuitry, such as amygdala–PFC white matter connectivity. Amygdala–orbitofrontal cortex (OFC) white matter connectivity has been linked to regulation of the amygdala’s response to emotional stimuli. Using a preregistered analysis plan, we prospectively examined the effects of childhood exposure to two dimensions of adversity, viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
0
10
1
Order By: Relevance
“…It may be that an examination of initial levels (i.e., harsh parenting in early childhood) versus changes thereafter (i.e., the trajectory of harsh parenting across childhood) will reveal more complex effects of adversity on corticolimbic function during socioemotional processing. This explicit focus on evaluating the timing of harsh parenting effects on corticolimbic function builds on previous work in this sample that has examined the cumulative (i.e., across childhood) effects of threat- and deprivation-related experiences of adversity on amygdala–prefrontal white matter connectivity (Goetschius, Hein, Mitchell et al, 2020), amygdala reactivity during socioemotional processing (Hein et al, 2020), and network-level resting-state functional connectivity (Goetschius, Hein, McLanahan et al, 2020)…”
Section: Environmental Effects On Corticolimbic Function: Considerati...mentioning
confidence: 99%
“…It may be that an examination of initial levels (i.e., harsh parenting in early childhood) versus changes thereafter (i.e., the trajectory of harsh parenting across childhood) will reveal more complex effects of adversity on corticolimbic function during socioemotional processing. This explicit focus on evaluating the timing of harsh parenting effects on corticolimbic function builds on previous work in this sample that has examined the cumulative (i.e., across childhood) effects of threat- and deprivation-related experiences of adversity on amygdala–prefrontal white matter connectivity (Goetschius, Hein, Mitchell et al, 2020), amygdala reactivity during socioemotional processing (Hein et al, 2020), and network-level resting-state functional connectivity (Goetschius, Hein, McLanahan et al, 2020)…”
Section: Environmental Effects On Corticolimbic Function: Considerati...mentioning
confidence: 99%
“…While frequently attributed to processes such as increased allostatic load [ 169 ], it may also be that exposure to multiple adversities up- or downregulates several neurodevelopmental processes that potentiate one another to exacerbate psychopathology risk. To this end, a recent study investigating white matter connectivity differences among adolescents who experienced adversity in childhood reported that, although there were no specific differences been individuals who experienced threat compared to social deprivation, there was a significant interaction between exposure to violence and social deprivation such that violence exposure only predicted white matter differences when social deprivation was high, but not when social deprivation was at mean or low levels [ 170 ]. This study illustrates that multiple co-occurring adversities or singular exposures can be studied through a dimensional lens to more comprehensively understand how dimensions of ELA are associated with the neurobiological mechanisms underlying psychopathology in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study examined how brain connectivity in adolescence might be affected by both childhood violence exposure and social deprivation (e.g., neglect, poor community cohesion) (Goetschius et al., 2020). The authors found that the combination of childhood violence exposure and social disadvantage correlated with reduced connectivity of the amygdala with the OFC and dorsomedial prefrontal cortex (i.e., the salience detection and mentalizing networks, respectively).…”
Section: Part I: Biopsychosocial Pathways To Violencementioning
confidence: 99%